Leveraging wearables to safeguard workers in a hotter climate - Margaret C. Morrissey; Jason Kai Wei Lee; Ian Rollo; Yannis Pitsiladis (Frontiers in Public Health, 2026)
Rises in global temperatures have threatened the health, safety, and productivity of workers who perform physically demanding work. Traditionally, occupational heat illness prevention plan have relied on environmental monitoring and administrative controls, however, these approaches do not account for the considerable intra- and inter-variability in physiological responses to extreme heat. In contrast, elite sport has served as a valuable test bed for investigating thermoregulation, exertional heat illness, and the feasibility of real-time physiological monitoring. Experiences from recent Olympic Games have demonstrated that integrated environmental and physiological monitoring systems can operate at scale under extreme heat conditions, while also highlighting important technological, operational, and governance limitations. Translating these advances to occupational settings presents both opportunities and challenges because workers differ substantially from athletes in age, health status, heat acclimatisation, work demands, exposure duration, and access to medical oversight. Furthermore, implementation is complicated by concerns regarding data governance, privacy, informed consent, device validity, interpretation of physiological information, and the use of physiological thresholds to guide workplace decisions. This commentary examines lessons learned from elite sport and discusses their application to occupational heatsafety programs. We propose a tiered adoption framework that aligns physiological monitoring complexity with organizational capacity, technical expertise, and governance requirements, ranging from foundational heat-safety practices to advanced multimodal physiological monitoring under professional oversight. Physiological monitoring should complement, but not replace, established heat-stress prevention strategies and be implemented within clearly defined operational and ethical boundaries. Future research should focus on validating wearable technologies in occupational environments, developing individualized decision frameworks, and establishing governance structures that support responsible implementation.